Entwicklungswerkzeuge für die Fahrzeugklimatisierung von Nutzfahrzeugen - Fritz, Michael (KIT Scientific Publishing, 2021)
The development of measures enhancing efficiency within a vehicle is very complex due to the interaction with other vehicle systems. Consequently, developers must be equipped with appropriate tools for successful execution of a development task. This book deals with ""simulation"" and ""complete vehicle test rig"" development tools for air conditioning systems in general and the efficient implementation and adaption of these two development tools for the fields of application of trucks.